How Earning Per Share (EPS) affects on share price and firm value - Khan, Tahsan Rahman; Islam, Md. Rashidul; Choudhury, Tonmoy Toufic; Adnan, Ashique Mahmood (© 2014 European Journal of Business and Management, 2016)
This article was published in European Journal of Business and Management [© 2014 European Journal of Business and Management ] and the definite version is available at : http://www.iiste.org/Journals/index.php/EJBM/article/viewFile/13572/13841 The article website is at: http://iiste.org/Journals/index.php/EJBM/article/view/13572/13841 The journal is licensed under a Creative Commons Attribution 3.0 Unported (CC BY 3.0) License.